Day 1 Wed, April 27, 2022 2022
DOI: 10.2118/209529-ms
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Cement Log Interpretation

Abstract: The Assisted Cement Log Interpretation project has used machine learning (ML) to create a tool that interprets cement logs by predicting a predefined set of annular condition codes used in the cement log interpretation process. The development of a cement log interpretation tool speeds up the log interpretation process and enables expert knowledge to be efficiently shared when training new professionals in the cased hole logging unit. By using high quality and consistent training data sets, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…The quality of the old cement sheaths may also be tested again to ensure that they are still effective. To date, pressure testing, cement bond logging, and variable density logging can evaluate the quality of the cement sheath [3]. However, pressure tests may not be economically feasible, and field experience has shown that, in some cases, pressure tests may cause damage to the cement sheath [4], whereas cement bond logging (CBL) and variable density logging (VDL) will not.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the old cement sheaths may also be tested again to ensure that they are still effective. To date, pressure testing, cement bond logging, and variable density logging can evaluate the quality of the cement sheath [3]. However, pressure tests may not be economically feasible, and field experience has shown that, in some cases, pressure tests may cause damage to the cement sheath [4], whereas cement bond logging (CBL) and variable density logging (VDL) will not.…”
Section: Introductionmentioning
confidence: 99%